1991
DOI: 10.1017/s0308229600020560
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of commercial steers, heifers and young bull carcases

Abstract: Consumers are becoming increasingly aware of dietary issues and are demanding that food is labelled effectively with compositional information. In the past 20 years major changes have taken place in beef production, in particular the greater use of young bulls and the introduction of genes from several continental breeds, which have the potential of producing leaner meat. The current standard reference, McCance and Widdowson's ‘The Composition of Foods’ was last revised over 10 years ago, so this trial was set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a result, the lipid content of tissues has declined and the fatty acid composition of lipid has moved in a 'healthier' direction. Kempster et al (1986); Lowe et al (1990); Wood et al (1989) As is shown in Table 1 there are several ways to describe the composition and fat content of meat. The figures in Table 1 show that the current P:S ratio in pigmeat is about 0.3 which compares with about 0.1 in beef and lamb.…”
Section: Recent Fatness Reductions In Uk Carcassesmentioning
confidence: 99%
“…As a result, the lipid content of tissues has declined and the fatty acid composition of lipid has moved in a 'healthier' direction. Kempster et al (1986); Lowe et al (1990); Wood et al (1989) As is shown in Table 1 there are several ways to describe the composition and fat content of meat. The figures in Table 1 show that the current P:S ratio in pigmeat is about 0.3 which compares with about 0.1 in beef and lamb.…”
Section: Recent Fatness Reductions In Uk Carcassesmentioning
confidence: 99%